PENGARUH PENGGUNAAN QRIS, PENDAPATAN, TABUNGAN dan GAYA HIDUP TERHADAP PERILAKU KONSUMTIF - Yudiana, Alifah Arum (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Needs are things that must be fulfilled in life. Humans cannot be separated from consumption activities to meet their daily needs. Humans also not only fulfill their basic needs but also their desire to get satisfaction. This gives rise to consumptive behavior. In addition, the development of an increasingly easy payment system also makes it easier for someone to consume. Income, savings and lifestyle also play a role in a person's consumption activity. This study aims to find out how the influence of the use of QRIS, income, savings and lifestyle on consumptive behavior so that later it is expected to be able to find out the factors that influence broader consumptive behavior. This research uses multiple linear regression method. The results of this study indicate that the use of QRIS, income and savings have no effect on consumptive behavior and lifestyle has a significant effect on consumptive behavior.